2009
DOI: 10.1017/s0025315409991202
|View full text |Cite
|
Sign up to set email alerts
|

Aplysina (Porifera: Demospongiae) species identification through SSCP-ITS patterns

Abstract: Keratose sponges have no spicules and limited robust morphological characters, causing severe problems for taxonomic classification. Single-strand conformational polymorphism (SSCP) analysis of PCR amplified internal transcribed spacers (ITS) of nuclear ribosomal RNA (rRNA) genes was used to elucidate speciation patterns in marine sponges of the genus Aplysina. In this study, Aplysina species with non-ambiguous traditional morphological alpha taxonomy were used to generate standard SSCP-ITS patterns, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Our study supports previous studies, in which the efficiency of this technique was demonstrated at distinguishing different species of microorganisms (Schwieger and Tebbe, 1998;MacGregor and Amann, 2006;Mohr and Tebbe, 2006), including sea sponges (Lamarão et al, 2010) and catfish (Sriphairoj et al, 2010), among others. In addition to identifying species, this technique has been indicated as a simple and accessible strategy for the validation of products processed from fish (Sriphairoj et al, 2010) and plants (Choa et al, 2011).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our study supports previous studies, in which the efficiency of this technique was demonstrated at distinguishing different species of microorganisms (Schwieger and Tebbe, 1998;MacGregor and Amann, 2006;Mohr and Tebbe, 2006), including sea sponges (Lamarão et al, 2010) and catfish (Sriphairoj et al, 2010), among others. In addition to identifying species, this technique has been indicated as a simple and accessible strategy for the validation of products processed from fish (Sriphairoj et al, 2010) and plants (Choa et al, 2011).…”
Section: Resultssupporting
confidence: 92%
“…Specifically, we tested the potential of the PCR-SSCP (polymerase chain reaction-single-strand conformation polymorphism) technique to develop a simple and rapid marker for the identification and molecular differentiation of Amazonian stingless bees using the COI (cytochrome oxidase I) and 16S rRNA (16S ribosomal RNA) regions of mitochondrial DNA. This technique has been extensively used, because it is sensitive to differences in DNA sequences, allowing the rapid processing of a large number of samples in the search for speciesspecific markers (Bastos et al, 2001;Lamarão et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we follow in this study previous researchers who have found small but consistent morphological (Erwin & Thacker, 2007) and molecular (Erwin & Thacker, 2007;Lamarao et al, 2010) differences between the Caribbean aplysinids and suggested that these be retained as separate species (see also discussion in Schmitt et al, 2005). Only six confirmed nucleotide differences, encoding two predicted amino acid changes, and no structural variation, were identified between these molecules.…”
Section: Discussionsupporting
confidence: 87%
“…Analysis of the genomes from A. fulva and A. cauliformis revealed that the mitochondrial subunit I of the cytochrome C oxidase (cox-1) sequence presents low levels of variation and thus we could not separate these related species ( Sperling et al, 2012 ). Instead, the internal transcribed spacer (ITS) was capable of differentiating several Aplysina species ( Lamarão et al, 2010 ). Nevertheless, neither cox-1 nor the ITS were capable to differentiate the Aplysina species investigated here.…”
Section: Discussionmentioning
confidence: 99%